PENDEKATAN SIYASAH SYAR’IYYAH & TAKHSHIS AL-QHADHI DALAM REFORMASI HUKUM KELUARGA DI NEGARA PAKISTAN - Ubaidillah, M. Burhanuddin; Mir’atul Hayah; Muhammad Sholahuddin (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2025)
The relationship between divine revelation (wahy) and reason (aql) must be positioned eclectically, complementing and supporting one another. This approach, as practiced by various countries in family law reform, aims to harmonize text and context. The transformation of Islamic law into positive law serves as an alternative solution to legal issues arising in society. Philosophically, if Islamic law remains stagnant, the gap between ideal and reality will widen, potentially leading to public frustration. Reconstruction is needed not only at the level of legal products (fiqh) but also in methodology (usul al-fiqh) to create an effective legal system. Abdullahi al-Na’im categorizes Islamic legal reform, particularly in family and inheritance law, into four models: (1) Takhshis al-Qadli (the authority of rulers to adjudicate and enforce court decisions), (2) Takhayyur or Talfiq (selection and combination of legal opinions), (3) reinterpretation of religious texts, and (4) siyasah shar’iyyah (state policies that align with Sharia). This article focuses on siyasah shar’iyyah and Takhshis al-Qadli in family law reform in Pakistan, the second-largest Muslim country. The study begins with an analysis of Pakistan’s historical and socio-cultural context, followed by its family law reform methods. The discussion covers reforms in polygamy laws, marriage registration, underage marriage, unilateral divorce, and dowry (mahr) and marriage expenses.